PEMANFAATAN MEDIA DAN TEKNOLOGI DI LINGKUNGAN BELAJAR ABAD 21 - Astry Nurbayanni; Dhea Ratnika; Ikaputera Waspada; Dadang Dahlan (Universitas Jabal Ghafur, 2023)
The application and adaptation of technology in the learning space has become a necessity to deal with changes in the globalization era. The development of information and communication technology has had a significant impact on the world of education, especially in the learning process. Innovation and creativity in learning have arisen thanks to technological developments. One of the learning concepts that has emerged is the use of digital media and the web and the internet to provide interactive and flexible learning experiences and assessments.Keywords: Technology, Learning, Assessment.